Insights into the selectivity mechanisms of grapevine NIP aquaporins - Sabir, Farzana (2020)
Nodulin 26-like intrinsic proteins (NIPs) of the plant aquaporin family majorly facilitate the transport of physiologically relevant solutes. The present study intended to investigate how substrate selectivity in grapevine NIPs is influenced by the aromatic/arginine (ar/R) selectivity filter within the pore and the possible underlying mechanisms. A mutational approach was used to interchange the ar/R residues between grapevine NIPs (VvTnNIP1;1 withUniversidade de Lisboa, VvTnNIP6;1, and VvTnNIP2;1 with VvTnNIP5;1). Their functional characterization by stopped-flow spectroscopy in Saccharomyces cerevisiae revealed that mutations in residues of H2/H5 helices in VvTnNIP1;1 and VvTnNIP6;1 caused a general decline in membrane glycerol permeability but did not impart the expected substrate conductivity in the mutants. This result suggests that ar/R filter substitution could alter the NIP channel activity, but it was not su cient to interchange their substrate preferences. Further, homology modeling analyses evidenced that variations in the pore radius combined with the di erences in the channel’s physicochemical properties (hydrophilicity/hydrophobicity) may drive substrate selectivity. Furthermore, yeast growth assays showed that H5 residue substitution alleviated the sensitivity of VvTnNIP2;1 and VvTnNIP5;1 to As, B, and Se, implying importance of H5 sequence for substrate selection. These results contribute to the knowledge of the overall determinants of substrate selectivity in NIPs